Power, pleasure, and profit insatiable appetites from Machiavelli to Madison - Wotton, David (Cambridge The Belknap Press of Harvard University Press, 2018)
We pursue power, pleasure, and profit. We want as much as we can get, and we deploy instrumental reasoning―cost-benefit analysis―to get it. We judge ourselves and others by how well we succeed. It is a way of life and thought that seems natural, inevitable, and inescapable. As David Wootton shows, it is anything but. In Power, Pleasure, and Profit, he traces an intellectual and cultural revolution that replaced the older systems of Aristotelian ethics and Christian morality with the iron cage of instrumental reasoning that now gives shape and purpose to our lives.
Includes bibliographical references and index.
Keywords: Conduct of life -- History; Power (Social sciences) -- History; Values -- History; Enlightenment; Ambition -- History; Pleasure; Profit